Adolescent development and growing divides in the digital age . Issue 2 (30th June 2020) - Odgers, Candice L.; Jensen, Michaeline R.
Abstract : Adolescents are constantly connected to their devices, and concerns have been raised that this connectivity is damaging their development more generally, and their mental health in particular. Recent narrative reviews and meta-analyses do not support a strong linkage between the quantity of adolescents' digital technology engagement and mental health problems. Instead, it appears that offline vulnerabilities tend to mirror and shape online risks in ways that may further amplify mental health inequalities among youth. New approaches for supporting youth mental health, especially for vulnerable youth and those typically excluded from traditional services, are now both possible and required.